Fruit and Vegetable Consumption and Cognitive Disorders in Older Adults: A Meta-Analysis of Observational Studies - Zhou, Yuhan; Wang, Jieyuan; Cao, Limin; Shi, Mengyuan; Liu, Huiyuan; Zhao, Yuhong; Xia, Yang (Frontiers in Nutrition, 2022)
Objectives: The aim of this meta-analysis was to assess the quantitative associations between fruit and vegetable intake and cognitive disorders in older adults. Design: A meta-analysis. Setting and participants: We used the PubMed, Web of Science and Scopus databases for a literature search to 12 April 2022. We preliminarily retrieved 11,759 studies, 16 of which met the inclusion criteria (including six cross-sectional studies, nine cohort studies and one case-control study), incorporating 64,348 participants and 9,879 cases. Methods: Using the three databases, we identified observational studies exploring the association. The pooled odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using a random effects model. Results: Sixteen studies were included in the meta-analysis, and the results showed that increased fruit and vegetable consumption in older adults was associated with a decline in the prevalence of cognitive disorders (OR: 0.79, 95% CI: 0.76–0.83). Moreover, intake of fruits (OR: 0.83, 95 % CI: 0.77–0.89) and vegetables (OR: 0.75, 95 % CI: 0.70–0.80) alone were both associated with a lower prevalence of cognitive disorders. Subgroup analyses indicated that the intake of fruits and vegetables was associated with the prevalence of cognitive impairment (OR: 0.72, 95% CI: 0.76–0.80) and dementia (OR: 0.84, 95% CI: 0.78–0.91) but not Alzheimer's disease (OR: 0.88, 95% CI: 0.76–1.01). Conclusion and Implications: Our meta-analysis provides evidence that the intake of fruits and vegetables is inversely proportional and linearly associated with the prevalence of cognitive disorders in older adults. Future research is required to further investigate the preventive effects of the frequency, quantity, and duration of eating vegetables and fruits on cognitive disorders in older adults.